Emulsion-templated porous polymers prepared by thiol-ene and thiol-yne photopolymerisation using multifunctional acrylate and non-acrylate monomers. (22nd September 2017) - Chen, Chaoyi; Eissa, Ahmed M.; Schiller, Tara L.; Cameron, Neil R.
Abstract: The chemical and mechanical properties of macroporous polymer substrates play a crucial role in the determination of their end-application. The preparation of highly (macro)porous monolithic polymers (polyHIPEs) by emulsion templating and thiol-ene/yne photopolymerisation, using multifunctional acrylate, allyl ether and alkyne-based monomers with trimethylolpropane tris (3-mercaptopropionate) (TMPTMP), is described in this work. Issues associated with monomer solubility and/or stability of the produced high internal phase emulsions (HIPEs) are tackled. Scanning electron microscopy (SEM) is used to study the morphology and porosity (average void diameters) of the obtained materials. Due to the nature of the photoinitiated thiol-ene reactions, materials obtained from acrylate monomers display residual thiols that are quantified by a colourimetric (Ellman's) assay. Raman spectroscopy is also shown to be a complementary technique to evaluate the residual thiol content. The influence of the monomer functionality on the mechanical properties of the material is explored using compression tests. Significant differences in the surface functionality and mechanical behavior between materials prepared with comonomers able to homopolymerise (acrylates) and those unable to homopolymerise (allyl ethers; alkynes) are demonstrated. Graphical abstract: Highlights: Acrylate comonomers give materials with residual thiol functionalities. Non-acrylate monomers in contrast contain negligible residual thiols. Compressive mechanical behaviour ranges from highly elastic to rigid foams. Depending on comonomer functionality, compressive moduli vary from 0.2 to 84 kPa. Tunable mechanical properties and levels of residual thiol can be obtained.